Makna Kesadaran Sebagai Nilai Konseling Islam Bagi Santri Binaan - Muhammad Fikri Iskandar; Wawan Juandi, Wawan Juandi (Fakultas Dakwah Universitas Ibrahimy, 2022)
Awareness is the basis of emotional intelligence. The ability to regulate emotions over time is important for psychological insight and self-understanding. Someone who has emo- tional intelligence will try to realize his emotions when they control him. The purpose of this study is to describe the meaning of awareness as the value of Islamic counseling for fostered students at the Salafiyah Syafi’iyah Islamic Boarding School Sukorejo Situbondo. The met- hod used in this research is qualitative research with case study type. The result of this rese- arch is to give birth to diligent behavior, disciplined behavior and behavior obeying the rules.